Studying Factors in The Development of Opticochiasmal Arachnoiditis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
According to the Department of Health for the period from 2003 to 2008. the level of diseases of the nose, nasopharynx, tonsils and paranasal sinuses in the CIS countries increased by 1.5 times [3]. The average incidence rate per 1000 population, according to our research, was 28.2 cases, which exceeds the data for Russia (24 cases) and the Samara region (26 cases) [5, 6]. In the structure of diseases of the nose, nasopharynx, tonsils and paranasal sinuses among residents of Togliatti, chronic sinusitis predominates, the level of which increased from 47.3% (2003) to 55.7% (2008), which leads to opticochiasmatic arachnoiditis. The above determines the relevance of research in the field of practical ecology, biology and medicine.